Hyper-Personalization in Retail: Leveraging Data Science and Real-Time Streaming - Nitin Saksena (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Personalization has transformed from a luxury feature to a fundamental business necessity in today’s digital retail landscape. This comprehensive article explores the evolution from traditional personalization to hyper-personalization, examining the retail sector’s technological components, practical applications, and future implications. The article investigates how advanced technologies, including artificial intelligence, machine learning, and real-time data streaming, enable retailers to deliver highly individualized customer experiences. Through a detailed examination of implementation strategies, benefits, and impacts, this analysis demonstrates how retailers leverage sophisticated data science frameworks and dynamic experience customization to enhance customer engagement, improve operational efficiency, and drive business growth. The article particularly highlights the transformative impact of hyper-personalization in specific retail segments, such as apparel, while also exploring the quantifiable benefits for retailers and customers.